2020
DOI: 10.46578/humder.775365
|View full text |Cite
|
Sign up to set email alerts
|

Siirt ve Çevresinde Üretilen Otlu Peynirlerin Fizikokimyasal, Mikrobiyolojik ve Duyusal Özelliklerinin Belirlenmesi

Abstract: Bu çalışmada Siirt ili ve çevresinde üretilen ve satışa sunulan 16 adet salamura otlu peynirlerin genel fizikokimyasal, mikrobiyolojik ve duyusal analizleri yapılmıştır. Analizler sonucunda pH değeri 4.33-4.90, titrasyon asitliği (laktik asit cinsinden) %0.87-1.36 kuru madde %50.10-56.69, kül %5.21-5.77, tuz %6.08-7.28 ve yağ %18.93-21.09 değerleri arasında tespit edilmiştir. Toplam aerobik mezofilik bakteri sayısı ile maya-küf sayıları literatüre göre yüksek sayılarda belirlenmiştir. Ayrıca 1, 2, 4, 8, 10 ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…There are significant variations in the dry matter ratios of the cheeses that are sold, according to research. It was noted in other earlier research that the dry matter ratio of the Siirt Herby Cheeses sold was not typical (34)(35)(36). According to reports, the dry matter content of the cheeses sold at Bitlis, Hakkari, and Van Herby Cheeses varies significantly (21)(22)(23)(24)(25)(26)(27)(28)29,30,32).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are significant variations in the dry matter ratios of the cheeses that are sold, according to research. It was noted in other earlier research that the dry matter ratio of the Siirt Herby Cheeses sold was not typical (34)(35)(36). According to reports, the dry matter content of the cheeses sold at Bitlis, Hakkari, and Van Herby Cheeses varies significantly (21)(22)(23)(24)(25)(26)(27)(28)29,30,32).…”
Section: Discussionmentioning
confidence: 93%
“…It has been demonstrated, therefore, that the sanitary quality and contents of regional cheeses made by non-commercial businesses are subpar (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). According to reports, Siirt Herby Cheeses sold at points of sale do not meet norms for chemical and microbiological quality (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it is inevitable that the cheese produced from raw milk or retail curd cheese. It has been pointed out in previously made studies that Siirt herby cheese on sale have not met the regulatory criteria (6,23,24,27,51).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the chemical qualities of herby cheeses on sale have not founded in accordance with related standards (19)(20)(21)(22)(23). It has also been reported in the previously made studies that hygienic quality of cheese samples examined have not been determined to be good (14,(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation